Physical Computing: A Key Element of Modern Computer Science Education - Hodges, Steve; Sentance, Sue; Finney, Joe; Ball, Thomas (IEEE Computer, 2020)
A recent growth area in computer science education is physical computing, which involves combining software and hardware to build interactive physical systems that sense and respond to the real world. This article provides an overview of physical computing and its value in the classroom, using the BBC micro:bit as an example.